Dasatinib protects against acute respiratory distress syndrome via Nrf2‐regulated M2 macrophages polarization. Issue 8 (9th June 2021) - Liu, Zishuang; Chen, Shanshan; Zhang, Xinfeng; Liu, Fangfang; Yang, Kai; Du, Ge; Rui, Xi
Abstract: Dasatinib, a tyrosine kinase inhibitor, has a protective effect on experimental acute respiratory distress syndrome (ARDS). This study investigated the effect and mechanism of dasatinib in ARDS. C57BL/6 mice were administered with dasatinib (1 and 10 mg/kg) after lipopolysaccharide (LPS) treatment to evaluate the effect of dasatinib on white blood cells (WBC), neutrophils, lymphocytes and macrophages in bronchoalveolar lavage fluid (BALF). The levels and mRNA expressions of inflammation‐related cytokines in lung tissues and RAW 264.7 cells were detected by enzyme‐linked immunosorbent assay and quantitative real‐time PCR, respectively. The protein expressions of nuclear factor E2‐related factor 2 (Nrf2) and heme oxygenase 1 (HO1) were determined by Western blot. MTT assay was performed to detect the viability of RAW 264.7 cell. Rescue experiments were used to assess the effect of Nrf2 silencing on the LPS‐ and dasatinib‐treated mice. Under LPS treatment, levels of the WBC, neutrophils, lymphocytes and macrophages in BALF and mRNA expressions of IL‐6, TNF‐α and IL‐10 as well as expression of iNOS were increased, but the expression of arginase‐1 was inhibited, while no obvious changes of the protein expressions of Nrf2 and HO1 were observed. Dasatinib partially reversed the effects of LPS above, and further promoted the mRNA expression of IL‐10 and the protein expressions of Nrf2 and HO1, while Nrf2 silencing counteracted the effect of dasatinib. Dasatinib induced the polarization of M2 subtype of macrophages and alleviated LPS‐induced ARDS through activating Nrf2 signaling pathway, which may provide a new strategy for the treatment of ARDS.